Correlation between resident birds and anthropogenic noise and particulate matter: A case study at Kasetsart University, Bangkok, Thailand - Chankhao A. (2023)
Importance of the work: Urban ecosystems are among the most polluted due to anthropogenic development, with humans and wildlife being affected by this pollution. Objectives: To examine the presence of some birds and their correlation to pollution in the kind of anthropogenic noise and particulate matter (PM). Materials & Methods: Sixty bird species were identified in the case study, of which the individual presence of 21 common residents was analyzed for their correlation to pollution using negative binomial regression. Results: Seven species were significantly correlated to the pollution. Five species (Pycnonotus goiavier, Spilopelia chinensis, Pycnonotus conradi, Passer montanus and Copsychus saularis) had a negative relationship to anthropogenic noise, while two species (Dicaeum cruentatum and Columba livia) had a negative relationship to the particulate matter levels PM10 and PM2.5. The results suggested that 14 resident bird species had adapted to living in the urban ecosystem. Main finding: Suggested policies to minimize the impacts on bird populations on campus were: restricting vehicle access; controlling noise levels; controlling black exhaust smoke emission; and promoting car- and pollution-free travel.